Haemophilus infections in chickens 2: types of Haemophilus paragallinarum isolates from chickens with infectious coryza, in relation to Haemophilus gallinarum strain no. 221 - 271463 Akira Sawata; Katsumi Kume; Yasukiyo Nakase
42